A research report on "condom practise and satisfaction among newly married couples in Chitwan district". - Shrestha, Ram Bahadur (2012)
ABSTRACT: A condom is a barrier device most commonly used during sexual intercourse to reduce the probability of pregnancy and spreading sexually transmitted diseases (STIs-such as gonorrhea, syphilis, and HIV). The objective of the study is to study condom practice and its satisfaction among newly married couples. A descriptive cross section study was carried out in selected three wards by simple random sampling of Gunganagar VDC of Chitwan district. A total 67 respondents were taken by the census methods. Self-administered questionnaire was used to collected primary data from the respondents and was analyzed using SPSS (Statistical Product and Service Solutions) and other simple statistical tools. Among the newly married couple under my study : maximum ethnic groups are Brahmin, Kami, Gurung, Chetteri, Tharu, Tamang respectively and they were to be mostly from joint family(50%).Both the couple was literate, among them most of the respondents (33.33%) in the study have complete or running secondary level. Similarly 22.72% and 19.69% have complete or running higher secondary and graduate level respectively. Regarding to their wife maximum i.e. 30.30%had completed or running secondary level. The major economic sources of the respondents were business, agriculture and teacher respectively. All the respondent who have taken part in research have heard about condom, among them 36 (54.54%) respondent are using condom currently for avoiding child, child spacing and for protection from HIV\AIDS and 30(45.46%) are not using condom due to the wish of children, afraid of allergy, to have full fun etc .In the study most of the couple(33.33%) sex more than 20 times in a week, among them 38.88% are using condom all the time and 61.12% are not using condom all the time during sexual intercourse due to not fulfillment of sexual desire, irritating to use and getting allergy. After the use of condom most of respondent dispose in the fields (24.39%), toilets (19.51%),dustbins (10.96%), rivers (13.88%), and buried down (33.33%). Among the respondents who are using condom, 52.78%did not feel any type of different and 47.22%respondents feel some difference of using condom during sexual intercourse. Due to different reason like not fulfillment of sexual desire, irritating to use and allergy getting, most of male respondent are completely dissatisfied (22.24%),not so satisfied(19.44%), nearly satisfied (38.88%) and complete satisfied (19.44%) of using condom. From them 22.22% satisfied condom using up to 25%, 25.01%up to 50%, 22.22%up to 75% and 30.55%respondents give their view that condom provide satisfaction more than 90%. Regarding wife satisfaction, most of respondents (63.88%) do not knows about wife satisfaction, similarly 16.6% of respondents wife are completely satisfied of using condom and 8.33%of their wife feel nearly satisfied with condom using during sexual intercourse.